MANAGEMENT ESSENTIALS. FIVE HOW-TO BOOKS COMPILED AND CONDENSED FOR TODAY'S BUSY MANAGER ([Place of publication not identified] : The Asian Sources Media Group, 1994)
Volume 1. Tips on sales and marketing, overcoming resistance, financial management, corporate survival, and time management -- Volume 2. Tips on customer service, performance appraisals, careers, niche selling, and presentations.